Perbandingan Hukum Tentang Pelaksanaan Judicial Review Antara Negara Indonesia Dan Negara Jerman - Wardhana, Yoshelsa, Iswanto S.H.,M.H, H. Ali Mukti S.H.,M.Hum (2016)
System and mechanism for constitutional review (Judicial Review) has just been adopted into the constitutional system of Indonesia with the establishment of Constitutional Court. The function of judicial review of the Constitutional Court is to ensure that no law are incompatible with the constitution. Since the establishment of the Constitutional Court, the Constitutional Court's authority of judicial review in Indonesia remains solely decides in case of doubts regarding the formal or substantive compatibility of an Act with the The 1945 Constitution of the Republic of Indonesia. On the other hand, the Federal Constitutional Court of Germany has been carrying out judicial review long before the Constitutional Court of the Republic of Indonesia. The authority of the Federal Constitutional Court of Germany is not merely decide in case of doubts regarding the formal or substantive compatibility of an Act with the Basic Law, but also any law under statute with the Basic Law for the Federal Republic of Germany. This normative study examines the comparison of law on the judicial review proceedings between Germany and Indonesia. Keywords: Judicial Review, Comparative Law, Constitutional Court